2020
DOI: 10.1101/2020.05.19.20105999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 RNA concentrations in primary municipal sewage sludge as a leading indicator of COVID-19 outbreak dynamics

Abstract: We report a time course of SARS-CoV-2 RNA concentrations in primary sewage sludge during the Spring COVID-19 outbreak in a northeastern U.S. metropolitan area. SARS-CoV-2 RNA was detected in all environmental samples, and when adjusted for the time lag, the virus RNA concentrations tracked the COVID-19 epidemiological curve. SARS-CoV-2 RNA concentrations were a leading indicator of community infection ahead of compiled COVID-19 testing data and local hospital admissions. Decisions to implement or relax public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
183
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(201 citation statements)
references
References 17 publications
(20 reference statements)
10
183
1
3
Order By: Relevance
“…These results suggest that the increase in case counts may occur concurrently with or even precede the increase in SARS-CoV-2 RNA in wastewater, while the decline in SARS-CoV-2 RNA in wastewater may lag the decline in case counts. This temporal variation in RNA in wastewater versus case counts has been suggested by others 24,25,28,34 . Further, the long term shedding of the SARS-CoV-2 after negative nasopharyngeal swabs may account for the detection of RNA in wastewater after the decline in case counts 35 .…”
Section: Virus Rna Detection Frequency and Correlation With Covid-19 supporting
confidence: 74%
See 1 more Smart Citation
“…These results suggest that the increase in case counts may occur concurrently with or even precede the increase in SARS-CoV-2 RNA in wastewater, while the decline in SARS-CoV-2 RNA in wastewater may lag the decline in case counts. This temporal variation in RNA in wastewater versus case counts has been suggested by others 24,25,28,34 . Further, the long term shedding of the SARS-CoV-2 after negative nasopharyngeal swabs may account for the detection of RNA in wastewater after the decline in case counts 35 .…”
Section: Virus Rna Detection Frequency and Correlation With Covid-19 supporting
confidence: 74%
“…In this study, we evaluated the effect of incubation of SARS-CoV-2 RNA containing wastewater at different temperatures on the loss of RNA over time ( Overall, more viral SARS-CoV-2 RNA was detectable in the liquid phase (91 ± 12% by mass) of the wastewater influent compared to the RNA sorbed on the solids (9 ± 12% by mass). Others have reported the detection of the SARS-CoV-2 RNA on activated sludge in treatment plants 34,41 . Given that most wastewater is near neutral pH and the SARS-CoV-2 spike proteins have estimated isoelectric points around 5.4 and 5.3 42 , the virion positive core is likely surrounded by negatively charged envelopes and spikes in these wastewaters.…”
Section: Considerations On Virus Survival In Sewersheds and Sample Hamentioning
confidence: 99%
“…Similarly, there has been no evidence of contagion through wastewater, which might reflect SARS-CoV-2's instability in water and its sensitivity to disinfectants 9,[29][30][31][32][33][34] . Viral RNA can, nonetheless, be found in wastewater 33 , which has made monitoring of viral RNA load in sewage a promising tool for the epidemiological tracking of the pandemic [35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…Another study in a region of Spain with the lowest prevalence of COVID-19, detected the virus in wastewater before the first COVID-19 cases were reported 37 . A study from Yale University measured the concentration of SARS-CoV-2 RNA in sewage sludge and found that viral RNA concentrations were highest 3 days before peak hospital admissions of COVID-19 cases, and 7 days before peak community COVID-19 cases 40 . Also, Balboa et al, 49 confirmed the presence of SARS-CoV-2 in sludge.…”
Section: Introductionmentioning
confidence: 99%
“…The nding of SARS-CoV-2 RNA in untreated wastewater 37 and sewage 38 , is suggestive of, but certainly not proof of, the possibility for survival of infectious virus within these human waste streams reviewed in 35,39,40 . Unfortunately, there are, to our knowledge, no data on the detection or persistence of infectious SARS-CoV-2 in wastewater, and this topic, therefore, remains a knowledge gap 35,39,40 .…”
Section: Discussionmentioning
confidence: 99%